Factors Affecting Islamic Bank Financial Performance - Muhammad, Mumuh; Sarı, Emre Selçuk; Umarovich, Kholdorov Sardor; Takidah, Erika; Pertiwi, Risa Sari (Universitas Pendidikan Indonesia, 2024)
Purpose – This study aims to investigate the factors affecting financial performance in Islamic banks.Methodology - The quantitative approach is applied in this study with panel data analysis as analysis tool. This study measures the performance of Islamic Banks (IBs) in Türkiye and Indonesia. In total, there are 5 and 11 Islamic banks in Türkiye and Indonesia respectively used in this study, resulting 109 samples to analyze. Findings - The results show that bank size, capital ratio, operating expense ratio and inflation are found to be significant on Return on Avergae Assets (ROAA) positively. However, bank age and loan ratio do not have significant effect on ROAA. It is important to evaluate these factors to improve financial performance of Islamic bank in both countries as big Muslim population.